THE ROLE OF STUDENTS AS AGENT OF CHANGE FOR SUSTAINABLE LIVESTOCK FARMING DEVELOPMENT - ., AMAM; SAPUTRA, AHMAD DONI (Majalah Ilmiah Peternakan; Vol 24 No 2 (2021): Vol. 24 No. 2 (2021)DO - 10.24843/MIP.2021.v24.i02.p06, 2021)
Law of the Republic of Indonesia Number 12 of 2012 states that higher education is part of the national educa- tion system that has a strategic role in educating the nation’s life and advancing science and technology by paying attention to and applying humanities values as well as the sustainable culture and empowerment of the Indonesian nation. The research objective was to examine the role of students as agents of change in sustainable livestock far- ming development. The research variables consisted of students as academicians and 5 dimensions of sustainable livestock development (ecological, economical, socio-cultural, institutions, and technological). The research was conducted using a digital survey method with a likert scale questionnaire +1 to +5 using the google form feature. Respondents are students of the Animal Husbandry Study Program, Faculty of Agriculture, Universitas Jember. Data were analyzed partially using simple linear regression using IBM SPSS Statistics 26. The results showed that the role of students had a positive and significant effect on the ecological, the economical, the social-cultural, the institutional, and the technological. The conclusion of the research shows that students have a role as agents of change in sustainable livestock farming development. Research recommendations regarding the role of students in supporting sustainable livestock farming development deserve attention of stakeholders, moreover, this role can be implemented with the support of the independent learning curriculum according to the Circular of the Minister of Education and Culture Number 1 of 2020 concerning the Policy of Free Learning.